If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(d + -9) + 3(2d + 8) = 32 Reorder the terms: 4(-9 + d) + 3(2d + 8) = 32 (-9 * 4 + d * 4) + 3(2d + 8) = 32 (-36 + 4d) + 3(2d + 8) = 32 Reorder the terms: -36 + 4d + 3(8 + 2d) = 32 -36 + 4d + (8 * 3 + 2d * 3) = 32 -36 + 4d + (24 + 6d) = 32 Reorder the terms: -36 + 24 + 4d + 6d = 32 Combine like terms: -36 + 24 = -12 -12 + 4d + 6d = 32 Combine like terms: 4d + 6d = 10d -12 + 10d = 32 Solving -12 + 10d = 32 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 10d = 32 + 12 Combine like terms: -12 + 12 = 0 0 + 10d = 32 + 12 10d = 32 + 12 Combine like terms: 32 + 12 = 44 10d = 44 Divide each side by '10'. d = 4.4 Simplifying d = 4.4
| 6v-=42 | | 5=13-k | | (w+2)(w+2)-2(w+2)+9w=8 | | (5r-7s)(4r+3s)=0 | | .67(6h+3)=.33(3h-4)-h^2 | | (5r-7s)(4r+3s)=3 | | x^2+7x+49=0 | | 5w-3=12 | | 2b+3(3)=10 | | 4(d-5)+20=5-2d | | 2x=5y+13 | | (2a+3b)(5a-2b)=0 | | 8(2w-6)+4(-1-5w)=o | | (5y-3)(y+2)=0 | | 2.3=1.7+m | | 25=x^2+36 | | y-5=4 | | 2x-14=3(x+3)(x+3)-8x^2 | | y=6x+2 | | -6(x-2)+4(3-6x)=36 | | y^2-6+3y=4(y-5)(y-5)-12 | | (7y-1)(2y-3)=0 | | y^2=21 | | 3x+35=7(x+5)-4x | | -75+10x=105 | | 2x^2=228 | | -75+10x=05 | | .5(y+4)(y+4)-6(y+3)=7 | | 3(x-2)=9x-9-6x | | 3(x-2)=6x-4-3x | | 0=4x^2+19x-54 | | 3x-9=2x-4(x-1) |